Downregulation of Caveolin-1 Enhances Fusion of Human BeWo Choriocarcinoma Cells - Collett, Gavin P. (Public Library of Science, 2010)
BACKGROUND: Fusion of placental villous cytotrophoblasts with the overlying syncytiotrophoblast is essential for the maintenance of successful pregnancy, and disturbances in this process have been implicated in pathological conditions such as pre-eclampsia and intra-uterine growth retardation. Caveolin-1 has been shown to be expressed in human villous cytotrophoblast and to be downregulated during fusion into syncytiotrophoblast but it is unclear whether it plays a role in this process. METHODOLOGY/PRINCIPAL FINDINGS: We used RNA interference to determine whether caveolin-1 plays a role in differentiation and fusion in the BeWo choriocarcinoma cell line, a model of villous cytotrophoblast fusion. Assessment of cell fusion by desmosomal protein immunostaining revealed that cells transfected with caveolin-1 siRNA showed significantly enhanced fusion in response to treatment with dibutyryl cyclic AMP compared with cells transfected with a non-silencing control. Furthermore, caveolin-1 knockdown alone was sufficient to promote spontaneous fusion. In addition, biochemical differentiation, assessed by expression of placental alkaline phosphatase, was upregulated in caveolin-1 siRNA-transfected cells, with or without dbcAMP treatment. Assessment of Akt phosphorylation showed that caveolin-1 knockdown resulted in a significant reduction in phosphorylation at Thr(308). CONCLUSIONS/SIGNIFICANCE: Taken together, these results suggest that caveolin-1 regulates BeWo cell differentiation and fusion, possibly through a mechanism involving modulation of Akt activity.